The space of flows in latin america or the real situation of a passive knowledge society - Villanueva Mansilla, Eduardo (2008)
This research uses the concept of space of flows in order to imroduce rhe notion that Peru and also Latín America are versions of a "passive" information societyrhar is, a reflection of global tendencies but not focused on them. lt will be argued from two main aspects of this discussion: transformations according to the audiences created from media consumption; and intellectual properry conflicts, from consumption of pirated items and Darknet use